Surviving cancer while young A meta-ethnography through temporal, social, interactional and personal experiences of survival - Eva-Mari Andersen (Elsevier, 2022)
Today, in Western countries, a majority of children, adolescents, and young adults diagnosed with cancer are expected to survive, potentially and hopefully until old age. There is a need for research that expands our knowledge of the ways in which young adult cancer survivors are understood, understand themselves, and narrate their lives. This meta-ethnographic review addresses this need, through the synthesis of ten qualitative research articles exploring the narratives of young adult cancer survivors, with a main focus put on the experiences described by survivors under the age of 30. In the synthesis, the narrated experiences of the young adult cancer survivors are presented through temporal, social, interactional, and personal dimensions. Although complex and intrusive, and constantly calling the young adult cancer survivors to action, these experiences are described as being masked and silenced. Seen together, they present surviving cancer while young as a unique way of being in the world, and as a multifaceted phenomenon present in everyday life and in all arenas of life. In conclusion, the synthesis prompts exploring young adults' survival-related experiences as credible and independent subjects of knowledge, but also as a common and shared responsibility.